Biological evaluation of aromatic compounds as B-Lactamase inhibitors (2006)
ABSTRACT: The appearance of bacterial resitance due to β-lactamase enzyme is frequent in Colombia and it has important consequences in term of morbidity and mortality. The inhibitory evaluation of the β-lactamase enzyme of 5 compounds gave as a result more powerful compounds than clavulanic acid. The more active chalcones establish hydrogen bonds with Ser, Tyr and Lys amino acids, the high number of hydrogen bonds between the compound and the amino acid increases the affinity and the inhibitory activity. In accordance with the results, the compounds might inhibit irreversibly the β-lactamase enzyme.